2000
DOI: 10.1136/gut.46.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer and other endoscopic diagnoses in patients with benign dyspepsia

Abstract: Background-It has been suggested that endoscopy could be replaced with noninvasive assessment of helicobacter status in the initial work up of young dyspeptic patients without sinister symptoms. Aims-To determine the incidence of gastro-oesophageal malignancy in young dyspeptic patients. Methods-The Alberta Endoscopy Project captured clinical and demographic data on all endoscopies performed from April 1993 to February 1996 at four major adult hospitals in Alberta. The endoscopic and histological diagnosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 28 publications
2
34
1
3
Order By: Relevance
“…The studies, so far, reporting a high prevalence of alarm symptoms in gastro-intestinal malignancies are mainly retrospective and, according to these studies, up to 90% of patients with gastro-oesophageal malignancies present alarm symptoms at the time of endoscopy [14][15][16] . Large prospective cohort studies have achieved less significant results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies, so far, reporting a high prevalence of alarm symptoms in gastro-intestinal malignancies are mainly retrospective and, according to these studies, up to 90% of patients with gastro-oesophageal malignancies present alarm symptoms at the time of endoscopy [14][15][16] . Large prospective cohort studies have achieved less significant results.…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian (CADET) study, which examined 1021 patients referred from primary care units, without alarm symptoms, identified only 2 cancers [27] . Other studies have demonstrated that the endoscopic yield of cancer, in simple dyspepsia, is low and only very few of the identified cancers are resectable [15,28] . We do not know whether the incidence of malignancy in patients with uncomplicated dyspepsia is different from that in the non-dyspeptic population; but we do know that early gastro-intestinal cancers are asymptomatic and are usually diagnosed by chance in patients undergoing endoscopy for dyspeptic symptoms secondary to benign or functional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was also observed by Breslin et al where he found pyloric elongation in8% of cases. 12 Cases were first subjected to exploratory laparotomy. In 67% of cases the growth was limited to the pylorus and prepyloric region.…”
Section: Discussionmentioning
confidence: 99%
“…227 In the Western world, however, this contention does not seem to hold as gastrointestinal malignancy is extremely rare in dyspeptic patients below 45-50 years if alarm symptoms are not present. [228][229][230] If one chooses to test for H pylori one should first have knowledge of the reliability of the test results (its positive and negative predictive value). This is not only dependent on the characteristics of the test (sensitivity and specificity) but also on the prevalence of the infection in the population.…”
Section: Rationale and Limitations Of The Various Approaches Of The Dmentioning
confidence: 99%
“…In the absence of alarm symptoms malignancies are extremely rare under the age of 50. [228][229][230] Most patients can, therefore, safely be treated blindly with acid suppression. Endoscopy will not change the management in most of these patients.…”
Section: Rationale and Limitations Of The Various Approaches Of The Dmentioning
confidence: 99%